2018
DOI: 10.1017/s0142716418000474
|View full text |Cite
|
Sign up to set email alerts
|

How conceptualizing influences fluency in first and second language speech production

Abstract: When speaking in any language, speakers must conceptualize what they want to say before they can formulate and articulate their message. We present two experiments employing a novel experimental paradigm in which the formulating and articulating stages of speech production were kept identical across conditions of differing conceptualizing difficulty. We tracked the effect of difficulty in conceptualizing during the generation of speech (Experiment 1) and during the abandonment and regeneration of speech (Exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 37 publications
(60 reference statements)
1
12
0
Order By: Relevance
“…Although the study included different aspects and measures of utterance and cognitive fluency in both the L1 and the L2, there were measures that were not included in the analysis. For instance, whether and/or what kind of cognitive tasks to use in measuring processing involved in conceptualization (e.g., Felker, Klockmann, & de Jong, 2019) and L1 linguistic knowledge (e.g., grammar and vocabulary) could be addressed in future research. Another important avenue of future research is whether and how the relationship between utterance fluency and cognitive fluency in the L1 and the L2 changes over time with more experience in the L2.…”
Section: Resultsmentioning
confidence: 99%
“…Although the study included different aspects and measures of utterance and cognitive fluency in both the L1 and the L2, there were measures that were not included in the analysis. For instance, whether and/or what kind of cognitive tasks to use in measuring processing involved in conceptualization (e.g., Felker, Klockmann, & de Jong, 2019) and L1 linguistic knowledge (e.g., grammar and vocabulary) could be addressed in future research. Another important avenue of future research is whether and how the relationship between utterance fluency and cognitive fluency in the L1 and the L2 changes over time with more experience in the L2.…”
Section: Resultsmentioning
confidence: 99%
“…This is an important finding because mid‐clause pausing is believed to be linked to the formulation stage of the speech production process (Skehan, ). SLA researchers (e.g., Felker, Klockmann, & de Jong, ; Kahng, ) have long speculated that mid‐clause pausing during L2 speech highlights the speakers’ need to deal with the lexical and morphosyntactic demands of speech processing. Our findings support this view because they indicated that lack of phraseological knowledge increases the likelihood that learners will pause in an unpredictable manner.…”
Section: Discussionmentioning
confidence: 99%
“…In self-referential tasks, conceptualization may take longer but formulation is less constrained. These different cognitive demands may affect pausing patterns (Felker et al, 2019; Tavakoli & Wright, 2020), and possibly alter L1-L2 pausing relationships (Gagné et al, 2022). Nevertheless, other studies that found a strong L1-L2 link for Mid-ASU SPD also used picture narrations (Duran-Karaoz & Tavakoli, 2020; Peltonen, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The current study focused on utterance fluency as indexed by speed (syllable duration), breakdown (pausing behavior), and repair (repetitions and corrections) phenomena (Skehan, 2009). There is some evidence that these features reflect different aspects of speech processing (De Jong, 2016;Felker et al, 2019;Kormos, 2006;Segalowitz, 2010). For example, speed and pausing patterns may reflect conceptualization and formulation processes.…”
Section: Literature Reviewmentioning
confidence: 99%